Does Social Barriers Influence Women’s Intention toward Entrepreneurship? - Ali, Mohammad; Himel, Md Tanvir Alam (Journal of Social Economics Research, 2019)
This paper aims to investigate the impact of social and psychological barriers on the negative intention of female students to be an entrepreneur and to analyze the mediating role of psychological barriers between social barriers and negative entrepreneurial intention. Total of 791 female students were surveyed from Bangladesh through an on-line questionnaire. Four hypotheses have been developed and tested on the total sample. Structural equation modeling (SEM) is used to measure the validity of the data and the relationship among the variables. The study endorsed that social barriers have a significant negative association with the negative intention toward entrepreneurship that indicates social barriers do not significantly reduce the entrepreneurial intention. Psychological barriers as mediating variable have a significant and positive relationship with social barriers and those barriers also have a significant positive effect on negative intention toward entrepreneurship. Psychological barriers partially mediate the relationship between social barriers and the intention toward entrepreneurship. Thus, social barriers through psychological barriers significantly influence the entrepreneurial intention and reduce the inclination of female students toward entrepreneurship.